Pengaruh Identitas Politik Terhadap Regionalisme Timur Tengah: Integrasi Atau Disintegrasi? - Febriyanti, Auliya (Jurnal Transformasi Global, 2022)
The study of political identitiy in Middle East is an uniqe one due to the challenge that offered by both sub and supra identities. Sub-state identity indicates nationalism—loyal to its boundaries—and irredentism. Supra-state identity, Pan-Arabism and Pan-Islamism, that limit the loyalty to its state. Since Arab World and Islam World emerged in Middle East, this region became more integrated. This article will examine how political identities shape the region towards the integration. The theory of constructivism will play a significant role to analyize the impact of Middle East identites to conduct their foreign policy. The result of this study shows that Middle East countries’ foreign policies are mainly influenced by their identities as Arab nation and Islam nation. Both of these identities were created through historical interaction with the involvement of the external actors. Those identities shaped regionalism in Middle East through Arab League and Islamic Conference. However, it seems that the identities are collapsing since the institutions no longer functioned recently.Keywords: Political Identity, Regionalism, Middle East, Arab League, Islamic Conference Organization